Recombination-induced tag exchange to track old and new proteins - Verzijlbergen, Kitty F; Menendez-Benito, Victoria; van Welsem, Tibor; van Deventer, Sjoerd J; Lindstrom, Derek L; Ovaa, Huib; Neefjes, Jacques; Gottschling, Daniel E; van Leeuwen, Fred (Proceedings of the National Academy of Sciences - PNAS, 2010)
The dynamic behavior of proteins is critical for cellular homeostasis. However, analyzing dynamics of proteins and protein complexes in vivo has been difficult. Here we describe recombination-induced tag exchange (RITE), a genetic method that induces a permanent epitope-tag switch in the coding sequence after a hormone-induced activation of Cre recombinase. The time-controlled tag switch provides a unique ability to detect and separate old and new proteins in time and space, which opens up opportunities to investigate the dynamic behavior of proteins. We validated the technology by determining exchange of endogenous histones in chromatin by biochemical methods and by visualizing and quantifying replacement of old by new proteasomes in single cells by microscopy. RITE is widely applicable and allows probing spatiotemporal changes in protein properties by multiple methods.